Determinan Komitmen Afektif terhadap Profesionalisme Kerja - Saputro, Dedy; Mauludin, Hanif (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study examines the influence of position hierarchy and job promotion on work professionalism, with affective commitment as a mediating variable among employees of Lapas Kelas I Probolinggo (Class I Correctional Facility Probolinggo). Using a quantitative causal-explanatory design, data were collected from 103 respondents through structured questionnaires during January–May 2026 and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. Results indicate that all seven hypotheses are supported. Position hierarchy and job promotion each positively and significantly influence affective commitment and work professionalism, both directly and indirectly through affective commitment as a partial mediator. Position hierarchy emerged as the strongest direct predictor of professionalism, while job promotion was the strongest direct predictor of affective commitmentAffective commitment mediated approximately 38% of the total effect of job promotion on professionalism (indirect effect = 0.104; total effect = 0.274, based on PLS-SEM bootstrapping result). These findings underscore the importance of integrating structural management policies with psychological engagement strategies to foster sustained professional behavior in high-pressure public sector organizations.